APPLICATION OF ACCOUNTING MUDHARABA IN PT BANK SUMUT SYARIAH MEDAN BRANCH - Astuty, Widia (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
This study aims to determine the application of accounting mudaraba, namely the recognition, measurement, presentation and disclosure of PT. Bank Sumut Syariah Medan Branch. This research uses descriptive approach. Variables used are as seen from the mudaraba accounting recognition, measurement, presentation and disclosure. The data collection technique used is the technique of documentation and interviews. The author uses descriptive analysis method to analyze the data. The results showed that the application of accounting mudaraba at PT. Bank Sumut Syariah Medan Branch, namely: Recognition of mudaraba fund is not in accordance with PSAK No. 105 because the banks recognize it as mudharabah while under PSAK 105 mudaraba fund which is distributed on the delivery of cash or non-cash assets to customers are recognized as an investment mudaraba. Furthermore, the bank has the appropriate measurement application with PSAK No. 105 which mudaraba investment measured in accordance with the value recorded. Presentation of investment mudaraba not in accordance with PSAK No. 105 positioned as an investment due to the financing of current assets, according to PSAK 105 owners present mudaraba investment funds in the financial statements at the carrying amount, but the disclosure of the bank has implemented in accordance with PSAK No. 105 that the bank does not limit the distribution of profit sharing mudaraba business activities, to the presentation of its financial statements.Keywords : Accounting for Mudharabah, Recognition, Measurement, Presentation and Disclosure